2016
DOI: 10.1007/s10479-015-1970-x
|View full text |Cite
|
Sign up to set email alerts
|

Eco-efficiency measurement and material balance principle: an application in power plants Malmquist Luenberger Index

Abstract: Incorporating Material Balance Principle in industrial and agricultural performance measurement systems with pollutant factors has been on the rise in recent years. Many conventional methods of performance measurement have proven incompatible with the material flow conditions. This study will address the issue of eco-efficiency measurement adjusted for pollution, taking into account materials flow conditions and the Material Balance Principle (MBP) requirements, in order to provide 'real' measures of performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 52 publications
(93 reference statements)
0
18
0
Order By: Relevance
“…For example, the TRI (Toxics Release Inventory) has been a widely used aggregate index for land, water, and air emissions as it can compare company performances and reveal the effects of different regulations or economic tools [25,26]. Although there have been some informative studies in this area, shortcomings related to research object specialization and weak research method universality remain [27]. Another representative environmental performance evaluation method has been life cycle assessments (LCA); however, this had similar shortcomings [22].…”
Section: Environmental Performance Evaluationmentioning
confidence: 99%
“…For example, the TRI (Toxics Release Inventory) has been a widely used aggregate index for land, water, and air emissions as it can compare company performances and reveal the effects of different regulations or economic tools [25,26]. Although there have been some informative studies in this area, shortcomings related to research object specialization and weak research method universality remain [27]. Another representative environmental performance evaluation method has been life cycle assessments (LCA); however, this had similar shortcomings [22].…”
Section: Environmental Performance Evaluationmentioning
confidence: 99%
“…By using AHP and additive ratio assessment (ARAS) methods, Štreimikienė et al (2016) studied the Lithuanian electricity generation options and eventually concluded that nuclear power development was essential for power generation and the biomass power plant was the second choice for power generation. Also, several studies have investigated power plants evaluation in Iran (Arabi, 2014(Arabi, , 2016(Arabi, and 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To overcome this issue, Chung et al (1997) developed the Malmquist-Luenberger productivity index (MLPI) based on DDFs that takes into consideration simultaneously the desirable and undesirable outputs. The MLPI has been widely used in environmental productivity studies (e.g., Arabi et al, 2017;Bampatsou & Halkos, 2018;Jeon & Sickles, 2004;Kumar, 2006;Liu et al, 2018;Monastyrenko, 2017;Munisamy & Arabi, 2015;Shen et al, 2019;Song et al, 2017;Wang et al, 2013;Wei et al, 2019;Yörük & Zaim, 2005;C. Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%